Combined uterine and urinary bladder rupture: an unusual complication of obstructed labor in a primigravida - Takai IU; Abubakar A (Dove Medical Press, 2016)
Idris Usman Takai,1 Abdulkadir Abubakar2 1Department of Obstetrics and Gynaecology, 2Department of Surgery, Bayero University/Aminu Kano Teaching Hospital, Kano, Kano State, Nigeria Background: Combined uterine and urinary bladder rupture following prolonged obstructed labor is indeed a momentous uro-obstetric emergency. The urinary bladder involvement is distinctly rare in the absence of factors that predispose the bladder to be adherent to the lower uterine segment and is quite unusual in a primigravida. Objective: To report a rare case of uterine rupture involving urinary bladder secondary to a prolonged obstructed labor in a primigravida from a low resource setting. Case: A 17-year-old married unbooked primigravida who presented with a 3-day history of spontaneous onset of labor at term that was initially managed at home and later in a primary health care center where she had fundal pressure and oxytocin augmentation, respectively. The labor was complicated by combined uterine and urinary bladder rupture with sepsis. She was resuscitated and had exploratory laparotomy with uterine and urinary bladder repair. The postoperative period was uneventful and she was followed-up at the gynecology and family planning clinics. Conclusion: There is a need for community reawakening on the inherent risks of teenage pregnancy, bad obstetric practices, and unsupervised pregnancy, labor, and delivery, particularly in the rural settings as in the index patient. A high index of suspicion and prompt appropriate intervention will reduce the sequel of morbidity and occasional mortality from this predicament. Keywords: uterine rupture, bladder rupture, primigravida, labor